2021
DOI: 10.1029/2020je006595
|View full text |Cite
|
Sign up to set email alerts
|

The Detectability Limit of Organic Molecules Within Mars South Polar Laboratory Analogs

Abstract: Our neighboring planet, Mars, has increasingly been the target of scientific exploration and of particular interest are its geological history, current environmental conditions, and perhaps most importantly, its potential as a host for extraterrestrial life (Fairén et al., 2010). The polar caps of Mars have more recently emerged as an area of scientific interest due to their abundance of water ice and their dynamic nature, especially with the discovery of a possible stable body of liquid water beneath the Mart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Despite these discoveries, PAHs have not yet been directly detected on the surface of Mars, and it is suggested that the ultraviolet radiation from the Sun destroys them in a time frame of 4-9.6 sols (solar day as measured on Mars) without shielding (Dartnell et al 2012). The PAHs could be shielded in the south polar residual cap region by the present ice (Campbell et al 2021) or found in the subsurface soil. Although PAHs are thought to be destroyed over a short time frame on the surface of Mars due to the UV radiation, a number of PAHs could survive under Venus-like conditions, as they form stable solutions in concentrated sulfuric acid, among them perylene (Bains et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these discoveries, PAHs have not yet been directly detected on the surface of Mars, and it is suggested that the ultraviolet radiation from the Sun destroys them in a time frame of 4-9.6 sols (solar day as measured on Mars) without shielding (Dartnell et al 2012). The PAHs could be shielded in the south polar residual cap region by the present ice (Campbell et al 2021) or found in the subsurface soil. Although PAHs are thought to be destroyed over a short time frame on the surface of Mars due to the UV radiation, a number of PAHs could survive under Venus-like conditions, as they form stable solutions in concentrated sulfuric acid, among them perylene (Bains et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…SPICAM-IR nadir data were already successfully used for long-term atmospheric studies, such as water vapor and the O 2 emission mapping (Trokhimovskiy et al, 2015;Guslyakova et al, 2016), but have never been used for analysis of the surface reflectance. IR observations at high spectral resolution may also be useful for detecting impurities in ice, such as PAHs (Campbell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%